An Implementation of the Joint Inheritance Division of Ethnic Groups in Lampung, Indonesia - Zaelani, Abdul Qodir; Faisal, Faisal; Fajar, Mokhamad Samson; Hanif, Abdul (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2023)
Lampung is a distinct, diverse, and multi-ethnic province. Lampung's multi-ethnicity is worth investigating regarding inheritance distribution, specifically the inheritance of joint property. This study examines the implementation of ethnic group inheritance in Lampung and how it contributes to the paradigm shift of joint property. This investigation is field research in which data is gathered from informants and analyzed using a cultural approach. According to the analysis, implementing the division of joint property inheritance of ethnic groups in Lampung could be classified into multiple categories. First, the majority of joint inheritance property is distributed straight to offspring (both male and female. Second, only daughters are given the joint property inheritance. Third, only the son receives joint property inheritance. Fourth, if one of the parents passes away, some joint property inheritance is granted to the mother and father. Because the Lampung community is nearly entirely unfamiliar with joint property (gono gini), the joint property inheritance is promptly distributed into the four categories listed above. Although the cultural practice considerably influences the distribution of inheritance in connection to the family system and social protection factors, it has begun to shift with less to no influence by religious and social factors.